2013
DOI: 10.1186/1471-2458-13-358
|View full text |Cite
|
Sign up to set email alerts
|

Age-appropriate vaccination against measles and DPT-3 in India – closing the gaps

Abstract: BackgroundIn 2010, India accounted for 65,500 (47%) of the 139,300 measles-related deaths that occurred globally. Data on the quality of age-appropriate measles vaccination in rural India is sparse. We explored the following issues: (i) What proportion of Indian children were appropriately vaccinated against measles at 9 months of age, and DPT-3 at 4 months? (ii) Which health facilities administered measles vaccine to children prior to 9 months of age and DPT-3 prior to 14 weeks?MethodsWe analyzed data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…first-dose coverage for the measles vaccine must be ≥90% at the national level and ≥80% for each district); intensive surveillance activities supported by adequate laboratory support (outbreak and case-based surveillance assisted by laboratories to ensure serological/virological categorization); appropriate case management (including administration of vitamin A); and implementation of catch-up measles vaccination campaigns for children aged 9 months to 10 years in states with <80% evaluated coverage with the first dose of measles vaccine ( 12 , 13 ). Despite the presence of these effective strategies, the Indian District Level Health Survey–3 reported that only 30% of vaccinated infants received the measles vaccine at the recommended age of 9 months ( 14 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…first-dose coverage for the measles vaccine must be ≥90% at the national level and ≥80% for each district); intensive surveillance activities supported by adequate laboratory support (outbreak and case-based surveillance assisted by laboratories to ensure serological/virological categorization); appropriate case management (including administration of vitamin A); and implementation of catch-up measles vaccination campaigns for children aged 9 months to 10 years in states with <80% evaluated coverage with the first dose of measles vaccine ( 12 , 13 ). Despite the presence of these effective strategies, the Indian District Level Health Survey–3 reported that only 30% of vaccinated infants received the measles vaccine at the recommended age of 9 months ( 14 ).…”
mentioning
confidence: 99%
“…Policy makers and professional bodies have acknowledged the presence of various challenges and hindering factors; they are working in a concerted manner to improve all components of the measles immunization program (infrastructure support, manpower and other resources, laboratory assistance such as virological surveillance, the importance of continued surveillance, etc.) ( 4 , 14 , 17 , 24 ). However, a mechanism should be developed to obtain an accurate estimate of the vaccine coverage across the nation ( 12 ).…”
mentioning
confidence: 99%
“…In the same study BCG coverage was 98% at 1 year but only 38% of infants were vaccinated within the first week of life; the median delay for BCG was 1.7 weeks; similar delays were found for one coastal Kenyan district [23] . In an Indian study using vaccination card records only 31% of infants received DTP3 by 14 weeks [24] . A study examining the timing of vaccination in low and middle income countries, based on surveys and imputed data, found at 6 months median coverage was 82% (Interquartile Range [IQR]: 67–89%) for DTP1, 36% (IQR: 23–54) for DTP3, and 85% (IQR: 73–91) for BCG [11] .…”
Section: Discussionmentioning
confidence: 99%
“…A vaccinated child can acquire subclinical wild virus infection considering suboptimal coverage, and variable rates of seroprotection following measles vaccination in Indian children. 8 To address the second valid concern, the index case, as well as their both parents, had tested negative for HIV. In developing countries like India, HIV is always on the top of clinical differentials for neuroregression in infants and young children.…”
Section: Mahmood D Al-mendalawi Department Of Paediatrics Al-kindy Cmentioning
confidence: 99%